Immunogenicity, Efficacy, and Effectiveness of Two-Dose and Shorter Schedules of Hepatitis E Vaccine: A Systematic Review - Bilal Azam; Melanie Marti; Amit Goel; Rakesh Aggarwal (Vaccines)
Background: Hepatitis E virus (HEV) is a leading cause of acute viral hepatitis in adults. The schedule for HEV 239, the only approved anti-HEV vaccine, consists of three doses at 0, 1, and 6 months, which is unsuitable for use in emergency and outbreak situations where quick protection is desired. We, therefore, undertook a systematic review of data on immunogenicity, efficacy, and effectiveness of alternative accelerated schedules. Methods: Data sources on immunogenicity, efficacy, and effectiveness of the HEV 239 vaccine following accelerated schedules published between 22 January 2005 and February 2024 were identified from five electronic databases, and the relevant data were extracted. Results: The search identified seven relevant reports, including one phase II pre-licensure trial, three reports from the phase III licensure trial, and three post-licensure reports. In these studies, following administration of the HEV 239 vaccine in two doses at 0 and 1 month or a three-dose rapid (0, 7, and 21 days) schedule, anti-HEV antibody seroconversion rates were similar to and geometric mean concentrations of anti-HEV antibody were only slightly lower than those following the standard three-dose schedule. In individuals who were seropositive for anti-HEV antibodies at baseline, the antibody response persisted for several years irrespective of the number of vaccine doses, and in those who were seronegative at baseline, administration of two vaccine doses induced antibodies whose level remained substantially high till at least 13 months of follow-up. Administration of two doses was also associated with a high protective efficacy against HEV infection and associated disease. Conclusions: The available data indicate that two doses of HEV 239 administered one month apart confer sufficiently high antibody titers and protection for at least 13 months, a duration which should be adequate for its use as an outbreak control measure.